Emergence of colistin resistance in multidrug-resistant Klebsiella pneumoniae and Escherichia coli strains isolated from cancer patients - Mai M. Zafer; Hadir A. El-Mahallawy; Asmaa Abdulhak; Magdy A. Amin; Mohamed H. Al-Agamy; Hesham H. Radwan (BMC, 2019)
Abstract Background Colistin resistance is mainly driven by alterations in the Gram-negative outer membrane lipopolysaccharides and is caused, in most cases, by mutations in mgrB gene. However, the recent emergence of plasmid-encoded colistin resistance among Enterobacteriaceae strains represents a serious threat to global public health. In this paper we have investigated the rates of colistin resistance and the underlying mechanisms in 450 Klebsiella pneumoniae and Escherichia coli isolates obtained from cancer patients in Egypt. Methods Colistin susceptibility and minimum inhibitory concentrations were determined according to the European Committee on Antimicrobial Susceptibility Testing, by broth microdilution, and by E-test. The mcr-1, mcr-2 and mgrB genes were detected by PCR and then sequenced. Clonal diversity in colistin-resistant K. pneumoniae was evaluated by multilocus sequence typing. Results Forty (8.8%) colistin-resistant isolates, including 22 K. pneumoniae and 18 E. coli, were isolated over 18 months. Of these, 50% were carbapenem-resistant, out of which nine were bla OXA-48 and seven bla NDM-1 positive. The mechanisms of colistin resistance could be revealed only in three of the 40 resistant strains, being represented by mcr-1 in one bla NDM-1 -positive E. coli strain and in one K. pneumoniae ST11 and by mgrB mutations, detected in one K. pneumoniae isolate. None of the studied isolates harbored mcr-2. Conclusions Our results demonstrate a high frequency of colistin resistance in enterobacterial strains isolated from cancer patients, but a low prevalence of the most well known resistance mechanisms.